PENINGKATAN KEMAMPUAN GURU MELALUI PELATIHAN KEWIRAUSAHAAN DAN MOTIVASI MODEL PEMBELAJARAN DARING - W. Widjanarko; andrian andrian; Supardi; Jumawan; Hadita; Ch. Indra Putra; D. Kurniawan; Hafizah (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
The still occurring covid-19 pandemic in the city area of Bekasi has affected learning activities for students via online living rooms with a limited schedule, so requiring teachers to be innovative in providing online and creative learning time after the learning process. This activity is undertaken to provide increased ability and understanding for teachers at the elementary school of cendrawasih the city of Bekasi with entrepreneurship and online learning models. Teachers can look for alternatives in the online learning model and can fill time to start self-entrepreneurs so that the online learning process is less boring and the time after online learning activities to be more productive. This method of carrying out the activity is the direct delivery of talks and discussions. Materials provided include explanations and discussions about the concept of entrepreneurship, how to start self-entrepreneurs, motivations related to teaching activities by teachers, and example examples of online teaching models.